2009
DOI: 10.1016/j.ntt.2009.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Continued effects of prenatal cocaine use: Preschool development

Abstract: The relationship between prenatal cocaine use and preschooler's physical and cognitive development and behavioral characteristics was examined, controlling for other influences on child development. On average, children were 38.5 months old, women were 29.4 years old, had 12.3 years of education, and 47% were African American. During the first trimester, 18% of the women were frequent cocaine users (≥ 1 line/day). First trimester cocaine exposure predicted decreased head circumference at 3 years and lower scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
53
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 64 publications
11
53
0
Order By: Relevance
“…We have found persistent associations between PCE and child temperament and behavior problems at 1, 3, 7, and 10 years of age (Richardson et al, 2008(Richardson et al, , 2009, which is consistent with reviews suggesting that the behavior domain is most likely to be affected (Ackerman et al, 2010;Behnke et al, 2013;Buckingham-Howes et al, 2013). Others have also reported that PCE is associated with child or adolescent behavior problems, particularly externalizing behaviors such as aggression and delinquency (Bada et al, , 2012Bennett et al, 2007Bennett et al, , 2013DelaneyBlack et al, 2000;Fisher et al, 2011;McLaughlin et al, 2011;Minnes et al, 2010;Nordstrom Bailey et al, 2005;Sood et al, 2005;Whitaker et al, 2011).…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…We have found persistent associations between PCE and child temperament and behavior problems at 1, 3, 7, and 10 years of age (Richardson et al, 2008(Richardson et al, , 2009, which is consistent with reviews suggesting that the behavior domain is most likely to be affected (Ackerman et al, 2010;Behnke et al, 2013;Buckingham-Howes et al, 2013). Others have also reported that PCE is associated with child or adolescent behavior problems, particularly externalizing behaviors such as aggression and delinquency (Bada et al, , 2012Bennett et al, 2007Bennett et al, , 2013DelaneyBlack et al, 2000;Fisher et al, 2011;McLaughlin et al, 2011;Minnes et al, 2010;Nordstrom Bailey et al, 2005;Sood et al, 2005;Whitaker et al, 2011).…”
Section: Introductionsupporting
confidence: 85%
“…As we have reported at earlier ages (Richardson et al, 2008(Richardson et al, , 2009, offspring with PCE were significantly smaller at age 15 even after adjusting for factors such as gender, pubertal development, and maternal height. Each of the growth measures (weight, height, and head circumference) was affected by first trimester exposure.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…18 In studies of behavioral problems using the Child Behavior Checklist (CBCL), 19 cocaine exposure has been associated with externalizing and or internalizing behavior problems in children as young 3 years 20,21 through school age, 20,22,23 with specific behavioral syndromes of attention problems at ages 4, 24 6, 22 and 9 to 11 25 years, aggressive behavior at 3 21 and 7 22 years, anxiety/depression at 3 21 and 8 23 years, and withdrawn behavior at 3 years. 21 To the best of my knowledge, we present the first longitudinal study of behavioral problems associated with prenatal MA exposure adjusted for prenatal exposure to other drugs and environmental risk. 20,24,26 Similar to studies of cocaine exposure, the CBCL was first administered at 3 years of age, then at 5 years.…”
mentioning
confidence: 99%